Reducing plant awareness disparity through botanipedia-enhanced project-based learning - Bilbina , Kanza; Hernawati, Diana; Fitriani, Rita (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2026)
Plant awareness disparity (PAD) refers to the limited attention, appreciation, and positive attitudes toward plants, which may hinder biodiversity conservation. This study aimed to determine the effectiveness of botanipedia-enhanced project-based learning (PjBL) in reducing PAD among high school students. A quantitative quasi-experimental study using a nonequivalent control group design was conducted with 60 tenth-grade students from SMA Negeri 2 Tasikmalaya, divided into 30 students in the experimental class (X-2) and 30 students in the control class (X-3). PAD was measured using a 24-item questionnaire administered on a four-point Likert scale. The instrument demonstrated satisfactory construct and empirical validity and high internal consistency (Cronbach's α = 0.835). Because the data violated the normality assumption, Quade’s rank analysis of covariance (ANCOVA) was employed to compare posttest scores while controlling for baseline pretest differences. The analysis revealed a significant treatment effect on PAD (p = 0.015) with a moderate effect size (partial η² = 0.098). These findings indicate that integrating a digital botanical encyclopedia into PjBL is an effective strategy for reducing PAD among high school students.